2000
DOI: 10.1002/(sici)1098-1004(200001)15:1<116::aid-humu25>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Nine independentF9 mutations in the Mexican hemophilia B population: Nonrandom recurrences of point mutation events in the human germline

Abstract: The factor IX gene (F9) is a valuable model for studying germ-line mutations. Nine mutations were detected in nine Mexican patients with hemophilia B by direct sequencing using genomic amplification with transcript sequencing (GAWTS): six single base changes, one micro-deletion, and two large deletions. Germline origins of mutations were found in three of six families with sporadic cases. Curiously, the four independent single base substitutions which were not at CpG dinucleotides occurred at only two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…It is possible that the existence of only one large deletion may represent a characteristic feature for the Turkish population. Such differences between different populations have already been observed [22,23].…”
Section: Discussionmentioning
confidence: 57%
“…It is possible that the existence of only one large deletion may represent a characteristic feature for the Turkish population. Such differences between different populations have already been observed [22,23].…”
Section: Discussionmentioning
confidence: 57%
“…From a study of nine independent Mexican hemophilia B families (Jaloma-Cruz et al, 2000), we found a particular mechanism of recurrent mutagenesis by four single independent substitutions in two similar non-CpG sites at nucleotide positions 17,678 (C88Y, C88F) and 17,747 (C111S, C111Y) of factor IX gene (Table 1). Using a statistical test considering a mutation target of 439 nucleotide position non-CpG sites in the coding region of factor IX (where >96% of factor IX gene mutations occur), it was demonstrated that the observed mutations were nonrandom events (p = 0.0004) (Jaloma-Cruz et al, 2000).…”
Section: Unusual Mutagenesis Mechanism In the Mexican Hemophilia B Pomentioning
confidence: 99%
“…Using a statistical test considering a mutation target of 439 nucleotide position non-CpG sites in the coding region of factor IX (where >96% of factor IX gene mutations occur), it was demonstrated that the observed mutations were nonrandom events (p = 0.0004) (Jaloma-Cruz et al, 2000). These mutations were considered as first-line evidence of a mechanism of recurrent mutation in hemophilia involving unusual hot-spot sites.…”
Section: Unusual Mutagenesis Mechanism In the Mexican Hemophilia B Pomentioning
confidence: 99%
See 2 more Smart Citations